أثر الألعاب و التطبيقات الالكترونية الصوتية في خفض شدة التلعثم دراسة ميدانية على مجموعة من الأطفال في الأغواط - شيخة عيوانة; صبرينة بن تركي; السعدية زروق (My University, 2021)
The current study aimed to know the effect of games and electronic applications on reducing the severity of stuttering and to know if there are differences between the sexes in their vulnerability to games and electronic audio applications, as well as knowing the effect of feedback on reducing stuttering intensity The study was applied to a sample of 8 male and female children between the ages of 6 to 12 years, who are studying in the elementary and intermediate levels in the city of Laghaout. The design of one group experimental method was used, where a treatment program was applied to one group, prior measurements of the stuttering intensity was carried out and then also after the completion of the application of the program, the poste measurement of the stuttering intensity is made. And on this basis it is noted if there is an effect of games and electronic audio applications in reducing the severity of stuttering?  The study's hypothesis was as follows: - There are statistically significant differences in the severity of stuttering between the prior and poste measurements, attributable to the applied treatment program. - There are no differences in the poste measurement of stuttering due to the sex factor. The following tools were used: - Stuttering intensity measure for Nahla Al-Rifaai. - Voice electronic game. - Two electronic applications loaded on a tablet, and earphones. - Tight treatment program  Wilcoxon Statistical treatment test was used. And reached the following results: - There are statistically significant differences in the severity of stuttering between the prior and poste measurements due to the applied treatment program. - There are differences in poste measurement in the severity of stuttering due to the sex factor.